2021
DOI: 10.3389/fpubh.2021.603273
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and Anxiety Symptoms of Healthcare Workers in Intensive Care Unit Under the COVID-19 Epidemic: An Online Cross-Sectional Study in China

Abstract: Background: Since the coronavirus disease-2019 (COVID-19) outbreak, intensive care unit (ICU) healthcare workers were responsible for the critical infected patients. However, few studies focused on the mental health of ICU healthcare workers. This study aimed to investigate the psychological impact of COVID-19 on ICU healthcare workers in China.Methods: We distributed the nine-item Patient Health Questionnaire (PHQ-9) and seven-item General Anxiety Disorder questionnaire (GAD-7) online to ICU healthcare worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…A study of French ICU HCW, for example, reported anxiety and depression in 50.4% and 30.4% of respondents at the peak of the first wave [ 8 ]. Similarly, a study from China reported symptoms of anxiety and depression in 65.9% and 58.7% of ICU HCW during the deceleration phase of the first wave [ 20 ]. Finally, a study of ICU HCW in New York City revealed symptoms of anxiety and depression in 48% and 33% of respondents just after the peak of the first wave [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of French ICU HCW, for example, reported anxiety and depression in 50.4% and 30.4% of respondents at the peak of the first wave [ 8 ]. Similarly, a study from China reported symptoms of anxiety and depression in 65.9% and 58.7% of ICU HCW during the deceleration phase of the first wave [ 20 ]. Finally, a study of ICU HCW in New York City revealed symptoms of anxiety and depression in 48% and 33% of respondents just after the peak of the first wave [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, therapists in the neurology field experienced more anxiety than therapists working in pediatric or orthopedic areas. A possible explanation may be that therapists working in the neurological setting might worry about COVID-19 infection due to dealing with patients with low immune systems, especially those in the intensive care or neuro-surgery units ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants with middle-income level scored higher on anxiety or depression, probably because people of medium income level were in a period of rising careers, hence subjectively feeling more pressured and more prone to emotional problems. Previous research mainly focused on the connection between income reduction and emotional state ( Xing et al, 2020 ; Peng et al, 2021 ). Therefore, the impact of income level needs to be further verified by follow-up research.…”
Section: Discussionmentioning
confidence: 99%